What are the ethical issues surrounding 'intentional death' in different nursing roles? A critical review - Tolman, Sarah (2011)
BACKGROUND: The ethical aspects regarding the nurse‟s role in „intentional-death‟ is a highly controversial debate in contemporary nursing.